Description of two new species of munnopsid isopods (Crustacea: Isopoda: Asellota) from manganese nodules area of the Clarion-Clipperton Fracture Zone, Pacific Ocean - Malyutina, Marina V. (Zootaxa, 2011)
Two new species of deep sea asellotes of the family Munnopsidae, Rectisura slavai sp. nov. and Storthyngura yuzhmorgeo sp. nov. are described from the manganese nodules area in the Clarion-Clipperton Fracture Zone of the Pacific Ocean. The discovery of these new species allowed re-examination of the taxonomic position of two similar species, Storthyngura ? intermedia (Beddard, 1885) from the Northeastern Basin of the Pacific Ocean and Ilyarachna defecta Menzies & George, 1972 from the Peru-Chile Trench, eastern Pacific Ocean. The species are moved to the genera Rectisura Malyutina, 2003 and Storthyngura Vanhöffen, 1914, respectively. Additional composition and distribution of the species of the genera are presented.